Children with Autism as a New Professional Reality - Valitova, I. E. (Psychological Prospects Journal, 2011)
In the article the problems of professionals working with children having autistic disorders are considered. The notion “professional position” concern children having autistic disorders is described, the possible ways of its formation is substantiated.